1992
DOI: 10.1056/nejm199202273260901
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Corticosteroids in the Treatment of Acute Optic Neuritis

Abstract: Intravenous methylprednisolone followed by oral prednisone speeds the recovery of visual loss due to optic neuritis and results in slightly better vision at six months. Oral prednisone alone, as prescribed in this study, is an ineffective treatment and increases the risk of new episodes of optic neuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
736
1
17

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,185 publications
(770 citation statements)
references
References 18 publications
16
736
1
17
Order By: Relevance
“…Intravenous high dose methylprednisolone therapy, 1 g daily for 3 days, followed by oral prednisone therapy (1 mg per kg of body weight per day for 11 days) also accelerates recovery from acute optic neuritis compared to placebo. 24 The optimal dose of i.v. methylprednisolone therapy is unclear.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous high dose methylprednisolone therapy, 1 g daily for 3 days, followed by oral prednisone therapy (1 mg per kg of body weight per day for 11 days) also accelerates recovery from acute optic neuritis compared to placebo. 24 The optimal dose of i.v. methylprednisolone therapy is unclear.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
“…high dose methylprednisolone, oral prednisone alone in standard (intermediate) doses (1 mg per kg per day for 14 days) has no beneficial effect on acute optic neuritis compared to placebo and may increase the risk of new episodes of optic neuritis. 24 One study has reported that oral intermediate dose methylprednisolone therapy alone for 21 days (48 mg daily for 7 days, followed by 24 mg daily for 7 days and then 12 mg daily for 7 days) is equally as effective as i.v. high dose methylprednisolone therapy (1 g daily for 3 days) for the treatment of acute relapses of MS. 26 The authors recommended that oral intermediate dose corticosteroid therapy be used instead of i.v.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
“…Among patients with severe ON, an inverse relationship between pRNFL thickness (i.e., optic disc edema) and visual acuity was observed for nontreated patients, which is in agreement with previous findings (Beck et al., 1992; Henderson et al., 2010; Malik et al., 2014). The possible mechanism for the steroid treatment effect may involve a suppression of the inflammation associated with acute ON, which in turn may limit the neuronal damage and accelerate visual function recovery (Beck et al., 1992; Kapoor et al., 1998; Sellebjerg, Nielsen, Frederiksen, & Olesen, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism for the steroid treatment effect may involve a suppression of the inflammation associated with acute ON, which in turn may limit the neuronal damage and accelerate visual function recovery (Beck et al., 1992; Kapoor et al., 1998; Sellebjerg, Nielsen, Frederiksen, & Olesen, 1999). This is supported by the current study's observation that nontreated patients experienced an early reduction in the pRNFL thickness and a delayed improvement of visual acuity and color mixing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation